Changes in the lipid composition during the photo-induced conidiation of Trichoderma viride - Betina, V; Koman, V (Folia microbiologica, 1980)
The sporulating and nonsporulating mycelium of Trichoderma viride exhibited significant differences in the levels of triacylglycerols, sterol esters. fatty acids, gangliosides, phosphatidylethanolamine and sphingomyelin. Quantitative changes in the contents of polar and nonpolar lipids were observed also during the analyses of one-, two-, three-day-old sporulation zones in colonies subjected to repeated photo-induction. These findings are similar to the changes observed during the differentiation of other species of fungi.
Keywords: Light; metabolismus lipidů; Mitosporic Fungi; Trichoderma; mitosporické houby; světlo; Lipid Metabolism